Pathways to Sustainable Growth in Niger A World Bank Group Country Economic Memorandum (Country Economic Memorandum, 2022)
This country economic memorandum aims to support Niger's efforts to walk on a path conducive to a resilient and sustainable economic growth. It does so by attempting to answer the following five questions, each of which constitutes a separate chapter: (i) what were the salient structural characteristics of Niger's growth performance in the last 20 years; (ii) what are the margins to accelerate growth in the medium to long term; (iii) how can technology be a vehicle for private sector development; (iv) how can the country's large natural resource endowments be managed in a transparent way that benefits the whole population; and (v) how can the current disaster management framework be strengthened to increase resilience to natural shocks